A VIDA "EMOCIONAL" DAS COISAS E O SIGNIFICADO DOS NÃO HUMANOS. UMA ANÁLISE DO VALOR DOS OBJETOS NA VIDA COTIDIANA DOS RESIDENTES DE UMA COMUNIDADE TERAPÊUTICA - José Galdino Barreto Soares; Cleber Ori Cuti Martins (Argumentos, 2017)
This article analyzes the perceptions of the politicalof the students of two schools in Santa Maria -RS, one public and one private. In theoretical terms, two approaches that integrate Democratic Theory, one that understands Democracy as a process of competition for the vote among political leaderships, are taken into account, where less-verticalized and more pluralistic decisions are related to the positive perception of politics; and another, on the other hand, argues that the more horizontal participation tends to engender greater involvement with policy issues. In methodological terms, questionnaires were applied, forming a quantitative non-probalistic sample. The data indicate that private school and public school students have a positive perception of politics and governments not reversed in participatory interests. With this, the theoretical assumption that relates the positive perception of politics with a greater involvement and participation was not verified in this study.